The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.agsy.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Farm-level adaptation to climate change: The case of the Loam region in Belgium

Abstract: Few studies have addressed the topic of farmers' adaptation to climate change from a multidisciplinary perspective, because of the diculty in assessing their impacts. In view of the growing concern in the agricultural sector on this issue, we analyzed farmlevel adaptation through arable land-use changes in the specic case of the Loam region in Belgium. With this aim, we used an agro-economic model which considered 20-year series of current and projected simulated yields with and without considering additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Those who adapt to CC have aboveaverage returns from adaptation compared to what a random individual would have earned from non-adaption. This finding is consistent with previous studies (Abdulai & Huffman, 2014;Cachorro et al, 2018;Di Falco et al, 2011), but in contrast with Boonwichai et al (2019) and Lobell (2014) who point that the impact of adaptation on crops productivity would be dependent on the adopted adaptation technology; hence, best innovation would not necessarily affect positively farming profit. Since the correlation coefficient for the farmers that have decided to not take any adaptation measures is not statistically significant, one would conclude that the farmers who have not taken any adaptation do not better performed or worse return from adaptation compared to an individual taken randomly in the sample.…”
Section: Determinants Of the Decision Of Adaptation To CC And Impact On Soybean Farmers' Revenue In Togosupporting
confidence: 92%
“…Those who adapt to CC have aboveaverage returns from adaptation compared to what a random individual would have earned from non-adaption. This finding is consistent with previous studies (Abdulai & Huffman, 2014;Cachorro et al, 2018;Di Falco et al, 2011), but in contrast with Boonwichai et al (2019) and Lobell (2014) who point that the impact of adaptation on crops productivity would be dependent on the adopted adaptation technology; hence, best innovation would not necessarily affect positively farming profit. Since the correlation coefficient for the farmers that have decided to not take any adaptation measures is not statistically significant, one would conclude that the farmers who have not taken any adaptation do not better performed or worse return from adaptation compared to an individual taken randomly in the sample.…”
Section: Determinants Of the Decision Of Adaptation To CC And Impact On Soybean Farmers' Revenue In Togosupporting
confidence: 92%
“…Analyzing and ranking the factors of uncertainty, two key points emerged clearly: i) locations (Continental area vs. Mediterranean area), which heavily affected the rank of each factor; ii) the weight of a factor, in casu the ETP model, that is usually not considered in the ensemble modelling studies and therefore, can be considered as a "hidden factor". The main source of variability in rice (Bregaglio et al, 2017) and wheat (Olsen et al, 2007) yield prediction was the location under similar climatic pattern; in this context the soil characteristics can play a major role in determining yield, water consumption (Kersebaum and Nendel, 2014;De Frutos Cachorro et al, 2018) and water footprint, especially under rainfed conditions (as assessed in our study). The rank of "crop model" and "RCP scenario" factors underlined the different sensitivity of the models in simulating yield, water consumption and related WF according to different climatic patterns, soil water balance and atmospheric CO 2 concentration.…”
Section: Factors Of Uncertaintymentioning
confidence: 59%
“…In summary, our study indicated that the European wheat production sector has the potential to improve the current yield levels and take advantage of atmospheric CO 2 fertilization; a further boost would derive from irrigation, but the economic benefit of such practice does not seem adequate to justify the water supply (Ventrella et al, 2015;De Frutos Cachorro et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Adaptation planning deals with complex and vast scientific information, uncertainty and also a plethora of possible responses, when dealing with adaptation in complex systems such as those that include ecosystems and humans, namely agroforestry systems (Bizikova et al, 2014;Fei and McCarl, 2018;Vermeulen et al, 2013;Zandvoort et al, 2017). Although several climate adaptation frameworks have been developed to support adaptation planning (Bours, D. et al, 2013;Hernández-Morcillo et al, 2018;Mitter et al, 2018;Robert et al, 2016;Vermeulen et al, 2013;Vilà-Cabrera et al, 2018b), few studies have reported and discussed adaptation planning methods for the agriculture and forestry at the farm level or municipal level from a multidisciplinary perspective (de Frutos Cachorro et al, 2018;Robert et al, 2016). The complexity associated with climate adaptation of agriculture and forestry requires a tool that is field adequate, effective in reducing vulnerability, flexible or dynamic and also capable of engaging farmers and stakeholders in a planning process that goes beyond incremental adaptation and mere management of present risks and climate variability (Halofsky et al, 2018;Robert et al, 2016;Vilà-Cabrera et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%